2021
DOI: 10.1088/1755-1315/911/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Performance of six new superior varieties of rice on tidal swamp-land in South Kalimantan Province

Abstract: Rice is the staple food for millions of people of Indonesia which produced from many agroecology including tidal-swamp. The contribution of swampland to the national rice production is still lower than 2%. One of the indigenous knowledge of the tidal-swamp farmers is the massive use of local varieties which have low yield. Therefore, efforts to increase rice production in tidal-swampland of Barito Kuala Regency should consider the use of superior varieties. The purpose of this study was to find out performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Several studies in the peatland areas of South Sumatra have shown a large dependence of rural households on work in the agriculture, forestry, fisheries, and livestock sectors. The income contribution of the agriculture, forestry, fisheries, and livestock sectors is approximately 40-65% of the total income of rural households in the peatlands of South Sumatra [5,7,40,43,59]. In OKI, the contribution to income from the agriculture, forestry, fisheries, and livestock sectors ranges from 40.18% to 56.92% which is similar to [75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in the peatland areas of South Sumatra have shown a large dependence of rural households on work in the agriculture, forestry, fisheries, and livestock sectors. The income contribution of the agriculture, forestry, fisheries, and livestock sectors is approximately 40-65% of the total income of rural households in the peatlands of South Sumatra [5,7,40,43,59]. In OKI, the contribution to income from the agriculture, forestry, fisheries, and livestock sectors ranges from 40.18% to 56.92% which is similar to [75].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further research and product development are required. Peatlands, owing to their hydrotopographic characteristics, are suitable ecosystems for planting food crops, especially rice [59,60]. Cultivating rice using the Sonor method has become part of the local knowledge of the people living around the peatland, in addition to catching and/or raising fish, swamp buffaloes, and using Purun.…”
Section: Purun (Eleocharis Dulcis)mentioning
confidence: 99%
“…The contribution of swampland to the national rice production is still lower than 2% but it is possible to increase it considering the large area of land that has not been utilized. Therefore, swamp land is the future land for food production in Indonesia [10].…”
Section: Introductionmentioning
confidence: 99%
“…The advanced science and technology nowadays has answered many challenges on the efforts to increase rice productivity, such as the use of new varieties (Hasbianto et al, 2021), the optimal cropping systems (Abduh et al, 2020), the use of organic fertilizers (Amanullah et al, 2016), inorganic (Sheudzen et al, 2020), the soil amendment (Haque et al, 2021), the weed management (Parameswari and Srinivas, 2017), pests and diseases (Ning et al, 2017), and the postharvest (Danbaba et al, 2019). This information can be easily accessed through applications on android (Nutini et al, 2021).…”
Section: Introductionmentioning
confidence: 99%